2019
DOI: 10.1111/ijac.13221
|View full text |Cite
|
Sign up to set email alerts
|

Structural investigation of Al2O3 coatings by PECVD with a high deposition rate

Abstract: The deposition of alumina on thermal barrier coatings can effectively avoid hot corrosion and increase durability. Al 2 O 3 coatings were prepared on an yttria-stabilized zirconia (YSZ) substrate by plasma chemical vapor deposition (CVD). The effects of microwave power (P M ) and total pressure (P tot ) on the crystalline phase and microstructure of Al 2 O 3 coatings were investigated, and the effect of the mechanism on the deposition rate was also analyzed. The α-Al 2 O 3 coatings with a needle-like microstru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Due to its wear and corrosion resistance, high band gap and beneficial refractive index, aluminium oxide (Al2O3) is a popular coating, widely used in a variety of applications in, for instance, protective coatings, microelectronics, and optical devices. In particular, Al2O3 can act as a passivating layer, as an alternative gate dielectric oxide, 1,2 anti-corrosion and permeation barrier coating, [3][4][5][6] as well as surface enhancement coating in the cutting tool industry. 7,8 Thanks to high growth rates and comprehensive surface coverage, Al2O3 layers are frequently synthesized by metal-organic chemical vapour deposition (MOCVD), a widely used technique for the preparation of functional coatings.…”
Section: Introductionmentioning
confidence: 99%
“…Due to its wear and corrosion resistance, high band gap and beneficial refractive index, aluminium oxide (Al2O3) is a popular coating, widely used in a variety of applications in, for instance, protective coatings, microelectronics, and optical devices. In particular, Al2O3 can act as a passivating layer, as an alternative gate dielectric oxide, 1,2 anti-corrosion and permeation barrier coating, [3][4][5][6] as well as surface enhancement coating in the cutting tool industry. 7,8 Thanks to high growth rates and comprehensive surface coverage, Al2O3 layers are frequently synthesized by metal-organic chemical vapour deposition (MOCVD), a widely used technique for the preparation of functional coatings.…”
Section: Introductionmentioning
confidence: 99%
“…Abedi et al [11] revealed that PECVD coatings of TiSiCN and TiCN have shown very good tribological properties along with superior wear resistance. Zhang et al [12] have indicated that PECVD coatings of Al 2 O 3 with a high deposition rate in which alumina acted as a thermal barrier. Muthuraja et al [13] conducted experiments on PECVD-Chromium diamonds like carbon (Cr-DLC) coated nozzle needle surface and revealed that it is to wear protective.…”
Section: Introductionmentioning
confidence: 99%